САРЫ-АРҚАНЫҢ ҚЫНАЛАР ФЛОРАСЫНА ЖҮЙЕЛІК ТАЛДАУ (Experimental biology, 2015)
In the article is realizeded systematic analysis of the flora of lichens in the Sary-Arka area within Karkaraly and Aktogay regions. Were determined 292 species which belong to 92 genus and 31 families. Were revealled the 110 new species of lichens for investigation region, and 30 species of them are new for territory of Republic of Kazakhstan. Was organized comparative analysis of the lichen flora of two investigation territory.
Keywords: flora of lichens